Tularemia in Arkhangelsk region: clinical and epidemiological aspects - L. V. Titova; O. V. Samodova; E. A. Krieger; T. A. Gordienko; N. V. Kruglova; I. V. Shhepina; Yu. V. Gontova (Журнал инфектологии, 2016)
Aim: to analyze epidemiological and clinical features of tularemia cases diagnosed between 2010 and 2014 and to identify factors associated with complications.Methods: We conducted retrospective cohort study including all patients hospitalized with tularemia between 2010 and 2014.Results: Most of tularemia cases were diagnosed in July (20,8%) and August (57,1%) among adult females (63,6%). The most common forms were bubonic and ulcer-bubonic (89,6%). Buboes were commonly found in the upper femoral and groin regions (92,2%). Diagnostic errors were revealed in 54,1% of cases. The most frequent misdiagnoses were lymphadenitis and fever of unknown origin. Delay in effective antibiotic therapy was associated with an increased rate of complications.Conclusion: Tularemia has a diversity of clinical presentations. Doctors need to memorize the most common clinical signs of tularemia (fever and lymphadenitis) to make timely diagnosis.